2009
DOI: 10.1086/604713
|View full text |Cite
|
Sign up to set email alerts
|

A Multinational Survey of Risk Factors for Infection with Extended‐Spectrum β‐Lactamase–Producing Enterobacteriaceae in Nonhospitalized Patients

Abstract: Community-acquired ESBL-producing Enterobacteriaceae are now prevalent worldwide, necessitating international collaboration. Novel approaches are required to adequately address issues such as empirical treatment for severe community-acquired infection and infection control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
320
13
21

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 445 publications
(412 citation statements)
references
References 38 publications
41
320
13
21
Order By: Relevance
“…The findings of Reuland et al showing that the use of PPIs is a risk factor were confirmed [7]. In the present study, previous use of antibiotics and close contact with horses were not confirmed as being risk factors, although these determinants have been identified as risk factors in other studies [5,30].…”
Section: Discussionsupporting
confidence: 70%
“…The findings of Reuland et al showing that the use of PPIs is a risk factor were confirmed [7]. In the present study, previous use of antibiotics and close contact with horses were not confirmed as being risk factors, although these determinants have been identified as risk factors in other studies [5,30].…”
Section: Discussionsupporting
confidence: 70%
“…Higher nonsusceptibility rates were consistently associated (for at least 4 of the 6 classes of antibiotics tested and MDR) with an age of ≥65 years, nosocomial infection, and production of CTX-M-type enzymes (Table 3). Long-term hospitalizations leading to nosocomial infections and exposure to antibiotics have also been described by others as risk factors for the acquisition of ESBL-producing isolates (Ben-Ami et al, 2009;Lavigne et al, 2007). A protective association was found for other age groups than ≥65 years, for the acquisition of infections due to non-ESBL-producing isolates and for the community-acquired infections.…”
Section: R (%) Ir (%) R (%) Ir (%) R (%) Ir (%) R (%) Ir (%) R (%) Irmentioning
confidence: 65%
“…Aunque estas enfermedades se han visto asociadas a las infecciones por microorganismos productores de BLEE, resulta llamativo que las cifras reportadas en el presente estudio sean significativamente mayores respecto al estudio anteriormente mencionado, en el cual la hipertensión arterial fue la comorbilidad más frecuente (25,2%), seguida de diabetes mellitus con 21%, mientras que la enfermedad pulmonar obstructiva crónica y la enfermedad renal crónica estuvieron presentes solo en el 8 y el 6,5% de los casos, respectivamente 12 . Respecto a las condiciones previas de exposición, el 61,6% de los pacientes había sido hospitalizado en el último año por IVU, hecho que resalta la asociación entre las hospitalizaciones previas por IVU con la infección por cepas resistentes expuesta en estudios previos 7,8,13 . Llama la atención que en el presente estudio el 25% de los pacientes presentara uso previo de antibióticos, teniendo en cuenta la fuerte asociación existente entre el tratamiento previo con antibióticos y la infección por microorganismos BLEE, como cefuroxima (OR 21,42; IC 95%: 5,38-85,22) 14 y fluoroquinolonas (OR 12,8; IC 95%: 4,4-37,2) 15 .…”
Section: Resultsunclassified
“…Adicionalmente, las bacterias productoras de BLEE suelen tener resistencia cruzada con otros grupos de antibióticos como las fluoroquinolonas, aminoglucósidos y tetraciclinas 4 . Entre los factores de riesgo relacionados con infecciones por patógenos productores de BLEE en pacientes hospitalizados se encuentran un mayor tiempo de estancia hospitalaria, intubación, ventilación mecánica, cateterización arterial o urinaria, diabetes, insuficiencia renal, exposición previa a antibióticos e infección de vía urinaria (IVU) previa [5][6][7][8] . Establecer la epidemiología de infecciones por patógenos productores de BLEE resulta complicado, debido a diversos factores como la distribución geográ-fica, densidad de la población, condiciones hospitalarias, entre otros…”
Section: Introductionunclassified